(untitled) (European Journal of Marketing and Economics, 2025)
The pre-trial stage requires judicial attention as well as attention from solicitors representing the parties to the action to ensure that cases are managed and disposed within strict deadlines. This study recommends the use of management process activities that are commonly used by business organizations to manage civil cases in the Malaysian civil courts at the pre-trial stage. Therefore, the objectives of this study are; first, to examine whether the provisions under the Rules of Court 2012 are capable of delivering quality service in its role as the fortress of justice and how the understanding of management process can assist in the management and disposal of cases efficiently. The findings indicate that the activities of process management (namely planning, organizing, directing and controlling exercises) can be used as a practical guide for the court managers as well as solicitors acting for the parties to the action to understand the importance of abiding by the provisions of the Rules of Court 2012 so that the management and disposal of cases can be done in an efficient manner. Although this study does not analyze the various process management theories, it is expected that the preliminary findings might enrich present literature relating to the conduct of civil litigation and also provide an insight on possible adoption of a framework to be used as a guide in managing cases under the Rules of Court 2012.